2005
DOI: 10.1111/j.1471-4159.2005.03421.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of EFA6C, a third member of the EFA6 family, in adult mouse Purkinje cells

Abstract: Cellular and subcellular localization of EFA6C, a third member of the EFA6 family, in adult mouse Purkinje cells. J. Neurochem. 93, 674-685. Fig. 4 The effect of overexpression of FLAG-tagged wild and GEFdefective EFA6C on actin cytoskeleton and cell morphology of HeLa cells. HeLa cells were transfected with he expression vectors encoding FLAG-EFA6C or GEF-defective mutant of FLAG-EFA6C and stained with anti-FLAG (green), Alexa568-phalloidin (red) for F-actin, and DAPI (blue) for nuclei. Note that the overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…EFA6C is expressed exclusively in the cerebellar Purkinje cells (Matsuya et al . ), whereas EFA6D is widely expressed throughout the brain (Sakagami et al . ).…”
mentioning
confidence: 99%
“…EFA6C is expressed exclusively in the cerebellar Purkinje cells (Matsuya et al . ), whereas EFA6D is widely expressed throughout the brain (Sakagami et al . ).…”
mentioning
confidence: 99%
“…EFA6, the prototypical representative of the third group of ARF–GEFs, is more similar to the cytohesins but contains several coiled‐coil‐like and proline‐rich elements (19). The EFA6 subfamily consists of four members, EFA6a–d (19–23). In vitro , most ARF–GEFs are relatively promiscuous with respect to their exchange activity toward different ARF‐GTPases, with the exception of EFA6, which is a specific exchange factor for ARF6 (19).…”
Section: The Cytohesin Family Of Arf–gefsmentioning
confidence: 99%
“…In neurons, accumulating evidence indicates that Arf6 regulates a diverse array of neuronal processes related to neuronal morphogenesis and synaptic plasticity including: neuronal migration (Falace et al, ); the formation of axons (Hernandez‐Deviez et al, ), dendrites (Hernandez‐Deviez et al, ), and dendritic spines (Miyazaki et al, ; Choi et al, ; Raemaekers et al, ; Kim et al, ); axonal transport (Eva et al, ); the release and recycling of synaptic vesicles (Galas et al, ; Krauss et al, ); and the trafficking and synaptic expression of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionate (AMPA) receptors during hippocampal long‐term potentiation and depression (Scholz et al, ; Oku and Huganir, ; Zheng et al, ). Similar to other small GTPase pathways, in which regulatory proteins outnumber their target small GTPases (Bos et al, ), to date, multiple GEFs and GAPs for Arf6 have been identified, including cytohesin1–3 (Frank et al, ; Langille et al, ; El Azreq et al, ), guanine nucleotide exchange factor for Arf6 (EFA6A–D) (Franco et al, ; Derrien et al, ; Matsuya et al, ; Sakagami et al, ), and BRAG1–3 (Someya et al, ; Sakagami et al, ; Fukaya et al, ) as Arf6‐GEFs, and GIT1–2 (Vitale et al, ), SMAP1‐2 (Tanabe et al, ; Natsume et al, ), ACAP1–2 (Jackson et al, ), ADAP1 (Venkateswarlu et al, ), ARAP2 (Yoon et al, ), ARAP3 (Krugmann et al, ), and AGAP3 (Oku and Huganir, ) as Arf6‐GAPs. The existence of multiple GEFs and GAPs for Arf6 suggests that the spatiotemporal precision of Arf6 activation depends on these regulatory proteins.…”
mentioning
confidence: 99%
“…Of these, three EFA6 members (EFA6A, C, and D) are abundantly expressed in the brain. At the mRNA level, EFA6A is preferentially expressed in the forebrain and cerebellar granule cells (Suzuki et al, ; Sakagami et al, ), whereas EFA6C is restricted to cerebellar Purkinje cells (Matsuya et al, ). At the protein level, EFA6A and EFA6C have a somatodendritic localization (Matsuya et al, ; Sakagami et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation